Pengaruh Penilaian Kinerja terhadap Pengembangan Karir Karyawan - Atina Nabila Ahmad; Didit Darmawan; Rahayu Mardikaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The increasingly dynamic organizational environment demands strategic human resource management to maintain competitiveness and achieve organizational goals. Performance appraisal serves not only as an evaluation tool but also as the basis for decision-making regarding employee career development. This study aims to analyze the impact of performance appraisal on career development based on various empirical research findings. The method used is a Systematic Literature Review (SLR) with the PRISMA framework and a descriptive-qualitative approach. Data were obtained from scientific articles on Google Scholar, Garuda, and ScienceDirect containing quantitative studies from the 2022–2026 period. The data were then analyzed using narrative synthesis to identify patterns of relationships between performance appraisal and career development. The results of the study indicate that performance appraisal has a positive and significant effect on employee career development. An objective, transparent, and measurable appraisal system helps organizations identify employee potential, enhance competencies, determine training needs, and support promotions and career opportunities. These findings align with Performance Management Theory, Human Capital Theory, Goal-Setting Theory, and Expectancy Theory. Therefore, the integration of performance appraisal and career development is a key strategy in building a competent, productive, and sustainable workforce.